Predictability of asset returns and the efficient market hypothesis - Mohammad Hashem Pesaran (Institute for the Study of Labor (IZA), 2010)
This paper is concerned with empirical and theoretical basis of the Efficient Market Hypothesis (EMH). The paper begins with an overview of the statistical properties of asset returns at different frequencies (daily, weekly and monthly), and considers the evidence on return predictability, risk aversion and market efficiency. The paper then focuses on the theoretical foundation of the EMH, and show that market efficiency could co-exit with heterogeneous beliefs and individual irrationality so long as individual errors are cross sectionally weakly dependent in the sense defined by Chudik, Pesaran, and Tosetti (2010). But at times of market euphoria or gloom these individual errors are likely to become cross sectionally strongly dependent and the collective outcome could display significant departures from market efficiency. Market efficiency could be the norm, but it is likely to be punctuated with episodes of bubbles and crashes. The paper also considers if market inefficiencies (assuming that they exist) can be exploited for profit.
Keywords: G12; G14; 330; Market efficiency; predictability; heterogeneity of expectations; forecast averaging; equity premium puzzle; Kapitalertrag; Börsenkurs; Effizienzmarktthese; Erwartungstheorie; Prognoseverfahren; Equity Premium Puzzle; Theorie; Welt